2018
DOI: 10.3390/socsci7080122
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Belonging in Computing: The Role of Introductory Courses for Women and Underrepresented Minority Students

Abstract: Abstract:This study examines an aspect of gender and racial/ethnic gaps in undergraduate computing by focusing on sense of belonging among women and underrepresented minority (URM) introductory computing students. We examine change in sense of belonging during the introductory course as well as the predictors of belonging, with attention to conditional effects by gender and URM status. Results show that sense of belonging outcomes are a product of both incoming student characteristics and college environments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 46 publications
3
57
2
1
Order By: Relevance
“…Introductory science, technology, engineering, and math (STEM) courses often serve as undergraduate students’ introduction to STEM disciplines and associated majors. These courses offer opportunities to foster a sense of belonging in students and establish students’ science identities, especially for students from groups underrepresented in STEM (e.g., Schinske et al , 2016 ; Trujillo and Tanner, 2014 ; Sax et al , 2018 ). The first day of class may be an especially important time point, as it could be used to mitigate student concerns, establish course norms, communicate the importance of course activities, and increase student motivation through promoting positive student interactions and explanation of instructional choices ( DiClementi and Handelsman, 2005 ; Nilson, 2010 ; Chasteen, 2013 , 2020 ; Seidel and Tanner, 2013 ; Brazeal et al , 2016 ; Meaders et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Introductory science, technology, engineering, and math (STEM) courses often serve as undergraduate students’ introduction to STEM disciplines and associated majors. These courses offer opportunities to foster a sense of belonging in students and establish students’ science identities, especially for students from groups underrepresented in STEM (e.g., Schinske et al , 2016 ; Trujillo and Tanner, 2014 ; Sax et al , 2018 ). The first day of class may be an especially important time point, as it could be used to mitigate student concerns, establish course norms, communicate the importance of course activities, and increase student motivation through promoting positive student interactions and explanation of instructional choices ( DiClementi and Handelsman, 2005 ; Nilson, 2010 ; Chasteen, 2013 , 2020 ; Seidel and Tanner, 2013 ; Brazeal et al , 2016 ; Meaders et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…One US study on women and underrepresented postsecondary students in computing found that students who have a more communal orientation to their studies also report a weaker sense of belonging in computer science (Sax et al 2018). A communal orientation to education is especially important to Hispanics in general (Núñez et al 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…When defensive communication becomes habitual in a social context, distrust of others becomes the norm, resulting in a social environment privileging competition over cooperation. Other researchers have found reasons to attribute low representation of women (and other minority groups) to cultural factors in the discipline (for example, see Rasmussen and Håpnes (1991) and Sax et al (2018)).…”
Section: Novices Learning Programming In Csementioning
confidence: 99%